Structural, Optical and Electrical Properties of Bi1.5Zn0.92Nb1.5-6x/5WxO6.92 Pyrochlore Ceramics - (:unkn) unknown (UNIV FED SAO CARLOS, DEPT ENGENHARIA MATERIALS, 2021)
Herein, the structural, morphological, compositional, optical, electrical and dielectric properties of Bi1.5Zn0.92Nb1.5-6x/5WxO6.92 (BZN) solid solutions are reported. Tungsten substituted BZN ceramics which are fabricated by the solid state reaction technique exhibited solubility limits at substitution level below x=0.18. Remarkable engineering in the structural, optical, electrical and dielectric properties of the pyrochlore ceramics is achieved via W substitution. Namely, shrinkage in both of the lattice parameters and in the energy band gap accompanied with decrease in the microstrain, in the dielectric constant and in the electrical resistivity is observed upon increasing the W content below the solubility limit. The increase in the W content in the BZN ceramics enhances the densification of the pyrochlore and leads to higher light absorbability and larger crystallites growth. The temperature dependent electrical resistivity measurements has also shown that the pyrochlore exhibit thermal stability below 380 K.
Keywords: Bi1.5Zn0.92Nb1.5-6x/5WxO6.92; ceramics; XRD; resistivity; band gap; ENERGY-BAND GAP; COMPOSITES; GROWTH